Psychopathology : foundations for a contemporary understanding - Maddux, James E.; Winstead, Barbara A. (New York, NY : Routledge, 2012)
"This is the most up-to-date text about theory and research on the etiology and treatment of the most important psychological disorders. It is intended for first-year graduate students in clinical psychology, counseling psychology, and related fields. Readers will appreciate that the length, organization, content, and level and style of writing remain appropriate for the audience throughout. Thoroughly revised, this third edition continues to disseminate research- and empirically-supported information on psychopathology, while also challenging students to think critically, not just memorize information. New additions to the text include sections on dissociative disorders, dimensional approaches, the biological bases of psychopathology, developmental psychology, and a chapter on learning theories that lays out the principles of learning"--
Includes bibliographical references and index.
Keywords: Psychology, Pathological; MEDICAL / Mental Health; PSYCHOLOGY / General; PSYCHOLOGY / Psychopathology / General